What-clefts with adjectives in English: A corpus-based analysis - Wiliński, Jarosław (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2022)
This paper aims to investigate the what-cleft construction with adjectives and establish its structural, semantic, and distributional features by adopting frame semantics and usage-based construction grammar, exploiting the data from the Corpus of Contemporary American English (COCA), and applying quantitative corpus-based methodology. To this end, the author extracts the occurrences of the What be ADJ be-construction from a large corpus of naturally-occurring data, determines its structural, semantic, distributional, and discourse-functional properties, and identifies adjectives that are strongly associated with the construction in question. The paper makes a significant contribution to a growing body of literature on the what-cleft construction by conducting a qualitative and quantitative analysis of one of its variants, a grammatical pattern with adjectives that has not been hitherto investigated in much detail.